Markers of oxidative and antioxidative activity in female dogs with mammary gland tumour with and without additional vitamin E supplementation - Stavinohová, Renata; Lorenzová, Jana; Papežíková, Ivana; Borkovcová, Ivana; Pfeifr, Jakub; Lojek, Antonín; Mrázová, Markéta; Crha, Michal (Acta veterinaria Brno, 2012)
The present study determined markers of oxidative and antioxidative activity in dog females affected with mammary gland tumour compared to healthy ones. The effect of additional vitamin E supplementation on oxidative and antioxidative status was evaluated as well. The study included 29 female dogs divided into 4 groups (groups 1 and 2 included females with a mammary gland tumour; groups 3 and 4 included healthy female dogs). Additional vitamin supplement containing α-tocopherol was given to the females of groups 1 and 4. Dogs from groups 1 and 2 were anaesthetized before surgery (ovariohysterectomy and mastectomy); anaesthesia was used also in group 3, but without performeing surgery. The content of vitamin E (free α-tocopherol), marker of antioxidative status, was measured in blood serum by liquid chromatography. The concentration of thiobarbituric acid reactive substances, marker of oxidative status, in serum and concentrations of protein and non-protein thiol groups, markers of oxidative and antioxidative status, in blood serum and in red blood cells were measured colorimetrically. In females with a mammary gland tumour from group 2, concentration of thiobarbituric acid reactive substances was significantly higher than 14 days after surgery and compared to healthy ones as well. In females with a mammary gland tumour from group 2, concentration of protein thiol groups in serum was significantly lower and concentration of non-protein thiol groups in serum was significantly higher than in healthy controls. The values of protein thiols in erythrocytes in females with mammary gland tumour from group 1 were significantly higher before supplementation with vitamin E. The present study revealed that females with a mammary gland tumour were more burdened with oxidative stress compared to healthy dogs. The removal of the mammary gland tumour led to improvement of oxidative and antioxidative status. This is the first report focusing on the effect of additional α-tocopherol supplementation on reducing oxidative stress by increasing antioxidative activity in females affected with mammary gland tumour; however, we did not prove it.
Keywords: Sulfhydryl Compounds; Mastectomy; antioxidancia; Dogs; zvířata; psi; Antioxidants; ovarektomie; látky reagující s kyselinou thiobarbiturovou; Mammary Neoplasms, Animal; oxidační stres; nádory mléčné žlázy u zvířat; hysterektomie; sulfhydrylové sloučeniny; Oxidative Stress; alpha-Tocopherol; biologické markery; vitamin E; ženské pohlaví; Female; mastektomie; Animals; Thiobarbituric Acid Reactive Substances; alfa-tokoferol; Ovariectomy; Biomarkers; Hysterectomy; Vitamin E